THE RATIONALITY OF ANTIBIOTICS THERAPY TOWARD CHILDREN WITH TYPHOID FEVER AT M.M. DUNDA HOSPITAL - Tuloli, Teti Sutriyati; Moo, Dewi R (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Typhoid fever is an acute systemic infectious disease in the small intestine caused by Salmonella enterica serotype typhi (Salmonella typhi) having the symptoms of fever a week or more with impairment of the gastrointestinal tract with or without impaired consciousness. The purpose of this study was to determine the rationality of antibiotic therapy in pediatric patients at M.M Dunda Limboto Hospital. Methods: This research belongs to non-experimental descriptive with retrospective data retrieval. The data used were obtained from 83 medical records of childhood typhoid patients during 6 months (Juneâ€“November 2016) at the regional general hospital of M.M Dunda Limboto. These data were analyzed using the Gyssens criteria. Results: The results showed that the most antibiotics used by physicians were ceftriaxone 39% of the use of antibiotic quality which was category IIB 9%, category IIA 13%, and category 0 (rational) 52%. Conclusion: The rationality of antibiotic therapy in children with typhoid fever at M.M Dunda Limboto Hospital was 52% of the most antibiotics used, i.e. ceftriaxone (39%). Â